PERTUMBUHAN DAN KANDUNGAN SERAT BEBERAPA VARIETAS KENAF (Hibiscus cannabinus L.) - Ayu Aizatul Natasa; Elza ' Zuhry; Adiwirman ' ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The objective of this research was to determine the growth and fiber content of five kenaf varieties and find out the variety that able to give the best fiber yield. This research was conducted in the agricultural experimental unit, Agriculture Faculty, Riau University from May until September 2015. The study arranged experimentally using Randomized Block Design (RBD) consist of 5 treatments and 4 replications. Varieties those used are Karang Ploso 6, Karang Ploso 9, Karang Ploso 11, Karang Ploso 12 and Karang Ploso 14.The data were examined by analysis of variance and means separation by Honestly Significant Difference (HSD) test at 5%. The parameters those observed were flowering age, harvesting age, plant height, stem diameter, plant fresh weight, stem fresh weight, fiber dry weight, and ratio of stem fiber. Varieties of  Karang Ploso 6, Karang Ploso 9, Karang Ploso 12 dan Karang Ploso 14 has same plant height potential. Higher plant will produce longer fibers.   Keywords : kenaf, varieties, growth.